Bird functional and taxonomic diversity in xerophytic forests: contributing to balance bird conservation and livestock production - Barzan, Flavia Romina (2023)
Biodiversity is increasingly dependent on the ecological state of agricultural and livestock systems. Here, we assess the relationship between bird functional and taxonomic diversity and forest structure along a gradient in grazing intensity in xerophytic forests in Central-East Argentina. We found that bird functional diversity responds more to forest structure variables than taxonomic diversity. Further, we found a non-linear response of functional and taxonomic richness to grazing intensity, peaking at intermediate intensity. Mature forests with older trees and low grazing intensity favored a wider range of bird traits, such as seed dispersal and cavity nesters. In particular, taxonomic and functional diversity significantly increased with increasing canopy cover and DBH. In contrast, shrub encroachment, high grazing intensity, and the decrease of tree density and cover were associated with reduced functional diversity, affecting various nesting, foraging, and habitat requirements of birds. We recommend preserving high canopy cover and older trees and maintaining low grazing intensities to create a synergy between livestock production and biodiversity conservation.